From incidence to strategy: a systematic review in playing-related musculoskeletal disorders - Cardoso, Mário (2021)
The intense performance and repetitive movements for a long period of time contribute to the developing of musculoskeletal disorders in instrumental musicians. This study aims to identify the major musculoskeletal disorders in the practice of the musical instrument and reflect on strategies to be used in the music teaching and learning process to reduce the risk factors for future musculoskeletal disorders. A systematic review of English and non-English articles using PubMed, Web of Science, and Scopus from 2015-2019. Additional studies were identified by searching abstracts presented at Medical Problems of Performing Artists (2015-2019) and Psychology of Music (2015-2019). Search terms included a combination of the keyword's musculoskeletal disorders, instrumental musicians, and music (n=187). From the systematic analysis pain, disabilities of the arm, shoulder, hand, neck, back and shoulders and temporomandibular, cervical muscle disorders and postural asymmetries are the major musculoskeletal disorders in the practice of the musical instrument. It is important to define preventive strategies to prevent and reduce the development of PRMDs in practitioners and performers.